(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2023)
The research project presented below was carried out at the Luis Carlos Galán school in commune 4 of the municipality of Soacha, Cundinamarca. With 5 eleventh grade students. The research focused on our main objective, which is the impact of intercultural roots in the strengthening of peaceful coexistence of students in grade 11, that is, how the socialization of students from different cultures has been modified by living in the same space in aspects such as violence and other aspects that derive from it. The research focused on the research method, participatory action, which as mentioned by Negrete, 2009, p. 91 intends to "Stimulate positive indigenous values and start from their own historical, social, economic, political and cultural reality". It is from this that the way in which the techniques of information collection will be implemented is structured according to the objectives defined within the general project, in which the technique is the interview and the collection Instrument is the questionnaire, this research route was the one that allowed the results to be obtained to understand which were the intercultural characteristics that should be strengthened in the school for peaceful coexistence. Therefore, the final product of the research was the creation of a physical booklet with pedagogical, didactic and ludic strategies that gave reason to fulfill the objective of the research project.